The Mediating Role of Work Engagement in the Relationship Between Transactional Leadership and Workload with Turn-over Intention Among Part-Time Coffeeshop Workers in Pontianak City - Silverius Aldi; Endah Mayasari; Maria Christiana Iman Kalis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of transactional leadership and workload on turnover intention, with work engagement as a mediating variable among part-time workers in the coffeeshop industry in Pontianak City. Transactional leadership, which emphasizes a system of rewards and punishments, along with high workload, is presumed to influence employees’ emotional attachment to their jobs and subsequently affect their intention to leave. This research adopts a quantitative approach using the PLS-SEM method through SmartPLS 4.0 software, with data collected via a Likert-scale questionnaire. A total of 200 respondents were selected using purposive sampling. The results indicate that transactional leadership has a significant negative effect on turnover intention and a significant positive effect on work engagement. Workload has a significant positive effect on both work engagement and turnover intention. Furthermore, work engagement has a significant negative effect on turnover intention and is proven to mediate the effects of transactional leadership and workload on turnover intention. These findings highlight the critical role of work engagement in reducing employees' desire to leave, even when faced with high workloads and a transactional leadership style.